Encapsulation of Plant Viral Particles in Calcite Crystals. Issue 5 (26th March 2018) - Al‐Handawi, Marieh B.; Commins, Patrick; Shukla, Sourabh; Didier, Pascal; Tanaka, Masahiko; Raj, Gijo; Veliz, Frank A.; Pasricha, Renu; Steinmetz, Nicole F.; Naumov, Panče
Abstract: The concept of biomineralization and encapsulation of organic molecules into inorganic matrices to alter and enhance their physical properties has been evolved and perfected in natural systems. Being inspired by the natural biomineralization of foreign components into calcite, here the inclusion of a plant virus, cowpea mosaic virus (CPMV) of 5.4% by mass into crystals of calcite is reported. The viral particles are labeled with a fluorescent tag (Alexa Fluor 532), and are observed within the calcite matrix using confocal fluorescence microscopy. Upon encapsulation, the calcite crystals exhibit an irregular and aggregated morphology, as visualized with atomic force and electron microscopy. The viral particles protected inside the calcite crystals are able to resist harsh chemical agents. While spherical viral particles such as CPMV can be easily included in calcite, viruses such as the tobacco mosaic virus are not compatible with the host, presumably due to their high aspect ratio. The results provide a simple and scalable method to incorporate viral particles into inorganic matrix, and could prove useful in thermal stabilization of sensitive viral biological agents such as vaccines in the future. Abstract : Particles of the cowpea mosaic virus are successfully incorporated into calcite crystals. The particles are found to be randomly distributed throughout the crystal. The occlusion of viral particles in crystalline inorganic host matrices could be used to thermally stabilize vaccines and other biomolecules in the future.